RESEARCH OF THE STRESS-STRAIN STATE OF PIPELINES EXPOSED TO THE INFLUENCE OF LANDSLIDE MASSIF ON TRANSVERSE SLOPES - Pyrih, T. Yu.; Karabinovych, M. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
Engineering preparation of the route in mountainous conditions includes measures, the implementation of which makes it possible to carry out the main types of linear works strictly according to the schedule with optimal labor and material costs and the use of the necessary machines and mechanisms. These include the implementation of anti-landfall and anti-lanslide measures, clearing the route from forest and bushes, arranging of shelves and notches, temporary exits from the main roads and entrances to the route, repairing and strengthening existing road surfaces, bridges and crossings, arranging of culverts and drainage structures, intermediate platforms for storage and installation of pipes, as well as construction of crossings over small rivers, streams and ravines. In order to correctly solve the issues that are part of the engineering preparation of the route, the construction organization project, which is issued by the design institute as part of the technical project, must necessarily take into account the materials of the route survey in kind. The survey must be carried out before the release of working drawings in conjunction with construction organizations. The survey materials should determine the optimal transport schemes for the delivery of pipes, materials and heavy construction equipment to the route, the volumes and methods of work performance to prevent landfalls and landslides, the volumes and costs associated with the reconstruction of existing roads and bridges, as well as the construction of access roads and culverts on them, the volumes and costs associated with the construction of assembly and storage platforms specifically for each difficult section of the route with ascent and descent, as well as the methods of work performance on these sections of the route.